The Role of Role-Playing Approaches in Enhancing Learning Outcomes in Primary Social Studies - Burhan, Imron; Ridhoh, M. Yunasri; Musfirah, Musfirah (PT. Riset Press International, 2026)
This study aims to analyze the role of the role-playing learning model in improving students’ learning outcomes in primary school Social Studies through a literature review of 15 previous research articles. The review was conducted by examining various types of studies, including experiments, classroom action research, comparative studies, and descriptive research, to identify patterns of findings and factors influencing the effectiveness of role-playing. The results show that most studies reported improvements in students’ learning outcomes, learning activities, and conceptual understanding after the implementation of role-playing. This model has been proven to provide concrete learning experiences, increase student engagement, and foster communication and collaboration skills. However, some studies also found that improvements in learning outcomes were not always significant, especially when scenario planning, media support, and student readiness were not optimal. These variations indicate that the success of role-playing is strongly influenced by the context and quality of instructional implementation. Overall, this review confirms that role-playing has strong potential as an active learning strategy that can enhance Social Studies learning outcomes in primary schools. The findings are expected to serve as a reference for teachers in designing more effective applications of role-playing and as a foundation for future research on innovations in Social Studies learning.